A study of adolescent English learners' cognitive engagement in writing while using an automated content feedback system. Issue 1 (2nd January 2020) - Lee, Cynthia
Abstract: The aim of this article is to reveal the ways in which six 14- to 15-year-old second language (L2) learners, two each of high, mid, and low English proficiency levels were cognitively engaged in writing while using an automated content feedback program known as the Essay Critiquing System 2.0 in three out of five workshops in a Hong Kong secondary school. Through their video-recorded verbal reports and stimulated recalls, it was found that cognitive engagement was demonstrated by means of some composing strategies including questioning what and how to write, reading, reasoning and planning, making evaluative comments, and problem-solving strategies. Forty-eight strategies representing four types of mental activities, as well as six aspects of their writing were identified from the two sets of introspective data. Both sets of data showed that the three groups of adolescent language learners made mental efforts to complete their writing in their own ways. All of them were concerned with what to write most, followed by how to express themselves. Although the findings of the six case studies may not be generalizable, through introspections they indicate how the adolescent learners were stimulated to use the System and technology to help them enrich both content and language while writing. The introspective data also shed light on pedagogical implications regarding the use of the System or similar computer-assisted programs to assist writing. The present study contributes to the literature by enhancing our understanding of adolescent English learners' mental activities in a computer-assisted writing environment, an area which is not adequately researched.